Subsidiarity and Proportionality in the Shaping of EU Law on the Protection of the Environment - Dudaš, Atila (Zbornik radova Pravnog fakulteta u Novom Sadu, 2015)
The principle of subsidiarity was introduced into the primary sources of EU law by the Maastricht Treaty in 1992, as a norm of general application, in order to determine whether the Union can take action in areas that do not fall under its exclusive competence, that is in areas that could be governed both by the acts of the EU and that of the member states. The principle of subsidiary is based on the undisputedly appropriate idea that the citizens’ needs ought to be addressed at the level closest to them. It allows the Union to take action if and insofar the objectives of the proposed measure cannot be sufficiently achieved by action of member states, taking into account its scale and expected effects, while they could clearly be achieved more efficiently by measures of the Union. Even if the conditions of the use of competence based on the principle of subsidiarity are met, it is limited by the principle of proportionality, according to which the institutions of the EU may take action only within the confines of the objectives laid out in the primary sources of EU law. In concrete cases, however, the principle of subsidiarity is as a rule subject to differing interpretations, creating a constant field for confronting standpoints of the Commission and that of the member states. Yet, the number of cases in which the Court of Justice has decided on the application of principle of subsidiarity is very small (around twenty) so far, in which the Court demonstrated that it will not lightly overturn an EU action on the ground that it is not in compliance with the principle of subsidiarity. The Protocol on the Application of Principles of Subsidiarity and Proportionality, introduced by and attached to the Amsterdam Treaty, and taken over by the Lisbon Treaty, sets out a procedure in which the national assemblies of the member states gain right to give reasoned opinion as to why they consider that a legislative proposal of the Commission does not comply with subsidiarity, if the Commission grounds the exercise of competence on this principle. It is yet to be seen whether the new rules on the application of subsidiarity will enhance the cooperation between the institution of EU and member states and bring closer their, usually differing, opinions in concrete cases on the possibility of the Commission to use its competence based on subsidiarity. This issue gains special relevance in the area of the protection of the environment, since environmental challenges could hardly be handled adequately solely by the actions of member states, hence Community action is usually required. Sometimes, however, determining the right of the EU institutions to use competence under subsidiarity demonstrates some degree of arbitrariness. The new rules of the Treaty on the European Union and the Protocol on subsidiarity cannot remove dilemmas of this kind, but it can be reasonably expected that they will create a more efficient mechanism for the approximation of opinions of the institutions of the EU and that of the member states.